The moderating effect of physical and social environments on the relationship between perceived technology training and job commitment among academic staff at Nigerian universities - Isidore Ekpe; Norsiah Mat (Inderscience Enterprises Ltd, 2015)
The objective of this study was to examine the moderating effect of physical and social environments on the relationship between perceived technology training and perceived work commitment of academic staff at Nigerian Universities. A survey method was used to solicit responses from 152 academic staff members of three University Business Faculties in the North, East and West regions of Nigeria. Data were analysed using descriptive statistics and hierarchical regression. The results indicated that most lecturers who received technology training could not apply the knowledge in the classroom regarding the use of teaching aids due to limited functional infrastructure and equipments.